2014
DOI: 10.1371/journal.pone.0086791
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Evidence for Placental DNA Damage in Preeclampsia

Abstract: Preeclampsia (PE) is an idiopathic multisystem disease affecting 5–7% of pregnant women. Placental oxidative stress is a characteristic feature of PE and occurs when the production of reactive oxygen species (ROS) within the placenta overwhelms the intrinsic anti-oxidant defenses. We hypothesize that excessive oxidative DNA damage at the fetal-maternal interface coupled with a defective DNA damage/repair response is causally related to PE. Here we demonstrate that γH2AX (a sensitive marker of DNA damage) is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Genomic instability is not an area of cellular dysfunction that has been extensively studied in the placenta. However, there is compelling evidence that DNA damage contributes to placental pathologies, including pre‐eclampsia (Fujimaki et al, ; Hilali et al, ; Tadesse et al, ). This DNA damage is characterized by increased DNA double‐stranded breaks, as characterized by increased levels of γ‐H2AX foci formation (Tadesse et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic instability is not an area of cellular dysfunction that has been extensively studied in the placenta. However, there is compelling evidence that DNA damage contributes to placental pathologies, including pre‐eclampsia (Fujimaki et al, ; Hilali et al, ; Tadesse et al, ). This DNA damage is characterized by increased DNA double‐stranded breaks, as characterized by increased levels of γ‐H2AX foci formation (Tadesse et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is compelling evidence that DNA damage contributes to placental pathologies, including pre-eclampsia (Fujimaki et al, 2011;Hilali et al, 2013;Tadesse et al, 2014). This DNA damage is characterized by increased DNA double-stranded breaks, as characterized by increased levels of γ-H2AX foci formation (Tadesse et al, 2014). Future studies will revolve around understanding how BRCA1 influences DNA repair in placental cells.…”
mentioning
confidence: 99%
“…Both in vivo and in vitro [92] studies on placentas from PE patients have shown significantly higher expression of γH2AX vs. normotensive controls and they appear to be localized to the maternal cells of the decidua. A statistically significant hypomethylation of CpG sites in maternal systemic blood vessels has been shown in preeclamptic women compared to controls.…”
Section: Soluble Endoglin (Seng)mentioning
confidence: 99%
“…Normally, the increase in the levels of oxidative stress induced by pregnancy is promptly managed. It has been proposed that tissue damage secondary to unmanaged placental oxidative stress occurs when intrinsic mechanisms for management of oxidative stress cannot cope with the rates of placental production of ROS [106]. Increased levels of oxidative stress measured early in pregnancy (from 16 to 20 w.g.)…”
Section: Role Of the Individual Repair Capacity In The Constitution Omentioning
confidence: 99%
“…have been shown to reliably predict the development of preeclampsia later [107]. Elevated levels of products of lipid peroxidation, 8-hydroxydeoxyguanosine (8-OH-dG), phosphorylated H2AX (both markers for the presence of DNA damage) and intermediates signifying ongoing DNA repair of oxidative damage have been repeatedly demonstrated in placentas from pregnancies complicated by preeclampsia compared to placentas from normal pregnancies [104][105][106]108].…”
Section: Role Of the Individual Repair Capacity In The Constitution Omentioning
confidence: 99%